Chilling requirements and dormancy evolution in grapevine buds. - ANZANELLO, R. (2018)
Fluctuations in winter chilling availability impact bud dormancy and budburst. The objective of this work was to determine chilling requirements to induce and overcome endodormancy (dormancy controlled by chilling) of buds in different grape cultivars. "Chardonnay", "Merlot" and "Cabernet Sauvignon" shoots were collected in Veranópolis-RS vineyards in 2010, and submitted to a constant 3 °C temperature or daily cycles of 3/15 °C for 12/12h or 18/6h, until reaching 1120 chilling hours (CH, sum of hours with temperature ≤ 7.2 °C). Periodically, part of the samples in each treatment was transferred to 25 °C for budburst evaluation (green tip). Chilling requirements to induce and overcome endodormancy vary among cultivars, reaching a total of 136 CH for "Chardonnay", 298 CH for "Merlot" and 392 CH for "Cabernet Sauvignon". Of these, approximately 39, 53 and 91 CH are required for induction of endodormancy in the three cultivars, respectively. The thermal regimes tested (constant or alternating) do not influence the response pattern of each cultivar to cold, with 15 °C being inert in the CH accumulation process. In addition, time required to start budburst reduces with the increase in CH, at a rate of one day per 62 CH, without significant impacts on budburst uniformity. Index terms: Chilling hours; endodormancy; budburst; Vitis vinifera .